2021
DOI: 10.1098/rsif.2021.0324
|View full text |Cite
|
Sign up to set email alerts
|

Back to the bones: do muscle area assessment techniques predict functional evolution across a macroevolutionary radiation?

Abstract: Measures of attachment or accommodation area on the skeleton are a popular means of rapidly generating estimates of muscle proportions and functional performance for use in large-scale macroevolutionary studies. Herein, we provide the first evaluation of the accuracy of these muscle area assessment (MAA) techniques for estimating muscle proportions, force outputs and bone loading in a comparative macroevolutionary context using the rodent masticatory system as a case study. We find that MAA approaches perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Often, prominent muscle attachment sites on bones are linked to powerful muscles (Etienne et al, 2021a; Houtekamer & Sondaar, 1979; Martin et al, 2019; Toledo et al, 2015). However, there are other studies arguing that the assessment of a strong muscle based on the development of its insertion area is not well supported (Bates et al, 2021; Bello‐Hellegouarch et al, 2013). It is, therefore, not completely certain whether the developed attachment areas of the bony elements of P. minor may have corresponded to powerful muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Often, prominent muscle attachment sites on bones are linked to powerful muscles (Etienne et al, 2021a; Houtekamer & Sondaar, 1979; Martin et al, 2019; Toledo et al, 2015). However, there are other studies arguing that the assessment of a strong muscle based on the development of its insertion area is not well supported (Bates et al, 2021; Bello‐Hellegouarch et al, 2013). It is, therefore, not completely certain whether the developed attachment areas of the bony elements of P. minor may have corresponded to powerful muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The centroids of the attachment areas can either be estimated for extinct taxa 44 , 50 , 51 , 53 , 60 , 97 , 122 124 or measured/inferred from digitized attachment areas of extant taxa 69 , 73 , 74 , 78 , 79 , 88 , 125 . Additionally, we developed a code (Supplementary Information) to streamline musculoskeletal modelling workflows that now allows to directly calculate the attachment centroids and the attachment area for extinct and extant taxa from the vertices placed on the attachment area during the iterative polygonal muscle modelling approach presented herein (see Supplementary Information for muscle attachment definition) or for selected faces of a segmented muscle (i.e., diceCT or MRI) or selected faces of a muscle scar/attachment area on a bone, as follows.…”
Section: Methodsmentioning
confidence: 99%
“… 33 , 56 , 58 , 66 ), we present an approach similar to ‘box modelling’ 67 . In contrast to lofting a surface over multiple rings or curves (e.g., see 33 , 58 , 60 , 64 , 68 , 69 ) with only limited control, polygonal modelling allows adjustment of every vertex individually, to extrude new faces, as well as to create holes, which can later be filled (i.e., closed) again, allowing modelling of muscles with complex geometry (e.g., with multiple heads or tendons; see Supplementary Information). This new approach makes it possible to build the musculature in relatively low resolution and, therefore, permits quick adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…Sellers et al [ 22 ], Wilken et al [ 23 ], Cost et al [ 19 ]) takes into account both origin and attachment areas, as well as muscle length. Bates et al [ 31 ] compared the Thomason [ 17 ] dry skull method and an approach based on attachment areas and found that for both methods, muscle properties, bite force, bone stress and stress patterns were less accurate compared to data and models obtained from cadaver data.…”
Section: Introductionmentioning
confidence: 99%